Integration of Multiple Plasmonic and Co‐Catalyst Nanostructures on TiO2 Nanosheets for Visible‐Near‐Infrared Photocatalytic Hydrogen Evolution. Issue 12 (2nd February 2016) - Jiang, Wenya; Bai, Song; Wang, Limin; Wang, Xijun; Yang, Li; Li, Yanrui; Liu, Dong; Wang, Xiaonong; Li, Zhengquan; Jiang, Jun; Xiong, Yujie
Abstract : Utilization of visible and near‐infrared light has always been the pursuit of photocatalysis research. In this article, an approach is developed to integrate dual plasmonic nanostructures with TiO2 semiconductor nanosheets for photocatalytic hydrogen production in visible and near‐infrared spectral regions. Specifically, the Au nanocubes and nanocages used in this work can harvest visible and near‐infrared light, respectively, and generate and inject hot electrons into TiO2 . Meanwhile, Pd nanocubes that can trap the energetic electrons from TiO2 and efficiently participate in the hydrogen evolution reaction are employed as co‐catalysts for improved catalytic activity. Enabled by this unique integration design, the hydrogen production rate achieved is dramatically higher than those of its counterpart structures. This work represents a step toward the rational design of semiconductor–metal hybrid structures for broad‐spectrum photocatalysis. Abstract : Multiple plasmonic and co‐catalyst metal nanostructures are integrated on TiO2 nanosheets for photocatalytic hydrogen evolution under visible and near‐infrared light. Enabled by plasmonic hot electron injection and co‐catalyst surface activation, the hydrogen production rate achieved is dramatically higher than those of its counterpart structures.